Shariah Compliance Practice for Aquaculture Application:: Development of Sustainable Fish Pellet from Food Waste - Mat Nayan, Nadirul Hasraf; Hamzah, Mohd Syahir Anwar; Ng, Celine; Zainol, Nur Zainatul Nadra; Ariffin, Latifah Md; Kasmin, Ashari (Journal of Quranic Sciences and Research, 2021)
This paper reported on the development of a new formulated fish feed pellet prepared by an extrusion method and the effect towards water quality according to Syariah compliance practice. The obtained pellets showed an excellent combination of all ingredients using household waste such as fish waste, sugarcane fibre waste, chicken fats and used palm oil. As a result, the well-developed feed pellets exhibit a remarkable improvement in preserving water quality compared to commercialize fish feed pellet. The new formulated fish feed pellet has low turbidity value and Biochemical Oxygen Demand (BOD) level, which help in maintaining the quality of water. It was found that the new pellet may slightly reduce the pH of the water at the low composition of protein sources.